The Role of Private Health Care Financing in the Central and Eastern European Countries - Borda, Marta (Ekonomika, 2008)
The economic transformation process in the central and Eastern European (CEE) countries has included, among others, a thorough reform of the previous, centrally planned health care systems. Consequently, the contemporary health care systems functioning in these countries, despite common directions of changes, vary in the area of detailed aspects. The purpose of the paper is to provide an overview of private sources of the health care financing (including out-of-pocket payments and prepaid plans), which are considered to be an important component of each health care system. In the first part of the paper, the results of comparative analysis of total health expenditure incurred by the CEE countries between 2000 and 2004 are presented in order to indicate the main trends, problems and differences among the analysed states. Next, the main types of private health expenditure are described and their contribution to the health care financing is presented. Finally, voluntary health insurance offered in the Polish market, considered as an additional method of health care financing. is characterized.The obtained results allow to compare and evaluate the range of using private health care funds in the analysed countries during the last few years. Moreover, the results indicate a need for the further development of private methods of health care financing. which in practice can supplement or duplicate health care services delivered by the public sector.